Construction of an IFNAR1 knockout MDBK cell line using CRISPR/Cas9 and its effect on bovine virus replication - Geng, Yuanchen; Jiang, Chuanwen; Yang, Hao; Xia, Qing; Xu, Xiaowen; Yang, Kaihui; Yuan, Xinwei; Chen, Jianguo; Chen, Yingyu; Chen, Xi; Zhang, Lei; Hu, Changmin; et al. (Frontiers in Immunology, 2024)
The type I int erferon (IFN) pathway is important for eukaryotic cells to resist viral infection, as well as an impediment to efficient virus replication. Therefore, this study aims to create an IFNAR1 knockout (KO) Madin-Darby bovine kidney (MDBK) cell line using CRISPR/Cas9 and investigate its application and potential mechanism in increasing viral replication of bovines. The IFNAR1 KO cells showed increased titers of bovine viral diarrhea virus (BVDV) (1.5 log10), with bovine enterovirus and bovine parainfluenza virus type 3 (0.5-0.8 log10). RNA-seq revealed reduced expression of the genes related IFN-I pathways including IFNAR1, STAT3, IRF9, and SOCS3 in IFNAR1 KO cells compared with WT cells. In WT cells, 306 differentially expressed genes (DEGs) were identified between BVDV-infected and -uninfected cells. Of these, 128 up- and 178 down-regulated genes were mainly associated with growth cycle and biosynthesis, respectively. In IFNAR1 KO cells, 286 DEGs were identified, with 82 up-regulated genes were associated with signaling pathways, and 204 down-regulated genes. Further, 92 DEGs were overlapped between WT and IFNAR1 KO cells including ESM1, IL13RA2, and SLC25A34. Unique DEGs in WT cells were related to inflammation and immune regulation, whereas those unique in IFNAR1 KO cells involved in cell cycle regulation through pathways such as MAPK. Knocking down SLC25A34 and IL13RA2 in IFNAR1 KO cells increased BVDV replication by 0.3 log10 and 0.4 log10, respectively. Additionally, we constructed an IFNAR1/IFNAR2 double-knockout MDBK cell line, which further increased BVDV viral titers compared with IFNAR1 KO cells (0.6 log10). Overall, the IFNAR1 KO MDBK cell line can support better replication of bovine viruses and therefore provides a valuable tool for bovine virus research on viral pathogenesis and host innate immune response.